Analisis Faktor-Faktor Yang Mempengaruhi Pergerakan Indeks Harga Saham Gabungan (IHSG) Di Bursa Efek Indonesia (BEI) Tahun 2012-2014 - Dewi, Vina Sintya; , Drs. Triyono M.Si (2016)
IHSG is the notes on the changes or the stock price since its first circulated until at a certain time. There are several factors that can affect the IHSG, one of which is a macroeconomic factor. In this research, macroeconomic factors used is the rate of inflation, exchange rate, and interest rate SBI. The data is taken from the monthly closing price of each dependent and independent variables. The sampling method used in this study is the sample saturated and obtained a sample of 36 months of data closing price. The data used are secondary data collection methods of data documentation. The analysis tool used is multiple linear regression by the method of partial adjustment models (PAM). The results showed that simultaneous inflation and the exchange rate SBI significant effect only partially IHSG while exchange rate, and interest rate SBIsignificant effect on the Indonesia Stock Exchange (IDX).